Geo-hydrological hazard and risk zonation of Banganga watershed using GIS and remote sensing - Ghimire, Motilal (Journal of Nepal Geological Society, 2001)
The present study attempts to analyse the terrain elements and geo-hydrological processes operating on the Banganga watershed in western Nepal. The paper also assesses the hazard and risk to the land use, land cover, and settlements. The Banganga watershed is highly rugged, steep, and fragile. Based on GIS, a geo-hydrological hazard map, a vulnerability map, and a risk map were prepared. In the study area, the geo-hydrological processes are active and intense during the monsoon season. Instabilities are generally found on steep slopes with high relative relief, in areas underlain by the Siwaliks, and along the fault zones. The mass movements are more frequent on slopes covered by dense to moderately dense forest than on the agricultural land. The socio-economic significance of the hazard in the watershed is considerably high. About 8% of the agricultural land lies in the very high and high hazard zones. Similarly, 18 house s are located in the very hazard zone. 93 houses in the high hazard zone, 211 in the moderately high hazard zone, and the rest of 2,185 houses in the moderate and low hazard zones. The risk map generated by combining the hazard map and vulnerability map shows 14% of the area under the very high and high risk zones, 38% under the moderate risk zone, and 48% under the low risk zone.